Bullying and ill-treatment: insights from an Irish public sector workplace. Issue 4 (19th May 2022) - Hodgins, Margaret; Lewis, Duncan; Pursell, Lisa; Hogan, Victoria; MacCurtain, Sarah; Mannix-McNamara, Patricia
IMPACT: The authors examine the experiences of public sector workers in Ireland who had either been ill-treated or who worked to prevent ill-treatment and bullying in their organization. The authors demonstrate the limitations of providing a policy in the absence of understanding the need for implementation, and the need to understand how organizational culture is relevant to both the enactment and the amelioration of ill-treatment in the workplace. Training managers to be proactive and to be mindful of the need to ensure accountability is important, as well as communicating what is unacceptable in terms of behaviour and management style. ABSTRACT This paper explores the experiences of workers in a public sector organization in respect of workplace ill-treatment. The paper is based on 11 interviews which were part of the Irish Workplace Behaviour Study (2018). Workplace ill-treatment, and in particular workplace bullying, has been found to be more prevalent in public sector workplaces. Irish public sector workplaces have taken the brunt of severe austerity measures imposed by successive governments as part of the country's fiscal retrenchment policies between 2008 and 2016. The findings reported in this paper support Salin's (2003) model of 'Enabling, motivating, and precipitating structures', and are considered in the light of psychological contract breach in the context of New Public Management (NPM).